3D band-absorptive frequency selective rasorber : concept and analysis - Liu, Qi (2019)
This paper presents a 3D band-absorptive frequency selective rasorber (FSR). Such an FSR is absorptive within a specific band and almost transparent below the absorption band. The definition and evaluation of the band-absorptive FSR is initially provided and followed by the design concept of 3D FSR. An example is then proposed, whose unit cell is composed of 3D absorber and 3D band-stop FSS. An equivalent circuit model is established for understanding its operating principle. A prototype of the proposed 3D band-absorptive FSR is fabricated. The measured results show that it has an absorption band (|S11| ≤ −10 dB and |S21| ≤ −10 dB) from 4.21 to 6.51 GHz, with a thickness of 0.17 wavelength at 4.21 GHz. Moreover, |S21| is higher than −1 dB at the frequencies below 1.28 GHz. The proposed band-absorptive FSR can be used as radomes for low-frequency antennas in military communications or spectrum monitoring systems.